Petitioners and Rebels: Petitioning for Parliamentary Reform in Regency England. Issue 3 (2019) - Poole, Robert
Abstract : The national petitioning campaign for parliamentary reform in 1816–17 was the biggest such movement before Chartism. It generated more than 700 local petitions with approaching a million signatures, representing perhaps 25 percent of adult males and extending the political nation well into the working classes. It was particularly strong in the Lancashire manufacturing districts, where economic grievances such as hunger and exploitation were converted through petitioning into arguments for political reform. The moving figure was Major John Cartwright, a veteran reformer who emerges as a more radical figure than usually supposed. The rejection of so many petitions by Parliament provided a legitimation for remonstrance and resistance, feeding through into extraparliamentary protests such as the march of the Manchester "Blanketeers" in 1817 and the mass platform movement of 1819 and "Peterloo." The research combines a study of the petitions and the radical press with a close examination of the Home Office material, yielding insights into both grassroots organization and the strategies of the authorities, local and national. While the strategy of mass action was defeated by repression, the right of the unenfranchised masses to engage in political petitioning was conceded in principle long before the advent of formal democracy.